Public health perspective of a pentavalent meningococcal vaccine combining antigens of MenACWY-CRM and 4CMenB. Issue 5 (November 2022) - Bekkat-Berkani, Rafik; Fragapane, Elena; Preiss, Scott; Rappuoli, Rino; Sohn, Woo-Yun; Soumahoro, Lamine; Vadivelu, Kumaran
Highlights: Multivalent vaccines have contributed to improved IMD vaccine coverage. Multivalent vaccines have led to reduced IMD incidence of combined serogroups. Pentavalent MenABCWY combines antigenic components of MenACWY-CRM and 4CMenB. MenABCWY builds on clinical data and real-world evidence with MenACWY-CRM and 4CMenB. MenABCWY may provide global health benefits via practical and broad IMD protection. Summary: Objectives: Invasive meningococcal disease (IMD) is a life-threatening disease that can rapidly progress to death or leave survivors with severe, life-long sequelae. Five meningococcal serogroups (A, B, C, W and Y) account for nearly all IMD. Meningococcal serogroup distribution fluctuates over time across the world and age groups. Here, we consider the potential public health impact of a pentavalent MenABCWY vaccine developed to help further control meningococcal disease and improve immunisation rates. Results: The GSK MenABCWY vaccine combines the antigenic components of MenACWY-CRM (Menveo®) and 4CMenB (Bexsero®), building on a wide body of clinical experience and real-world evidence. Both approved vaccines have acceptable safety profiles, demonstrate immunogenicity, and are broadly used, including in national immunisation programmes in several countries. Since the advent of quadrivalent vaccines, public health in relation to IMD has improved, with a decline in the overall incidence of IMD and an increase in vaccine coverage. Conclusion: A pentavalent MenABCWY has the potential to provide further public health benefits through practical, broad IMD protection programmes encompassing serogroups A, B, C, W and Y, and is currently in late-stage development.